Ozone therapy restores immune dysfunction in refractory idiopathic granulomatous mastitis as a novel potential therapeutic approach - Cabıoğlu, Neslihan; Çetin Aktaş, Esin; Emiroğlu, Selman; Tükenmez, Mustafa; Özkurt, Enver; Müslümanoğlu, Mahmut; İğci, Abdullah; Özmen, Vahit; Deniz, Günnur; Dinççağ, Ahmet Sait; Güven, Yusuf İzzettin (Wiley, 2023)
Immunological dysfunction has been suggested to play a major role in the pathogenesis of idiopathic granulomatous mastitis (IGM). We recently showed that ozone therapy was effective in patients with steroid-resistant IGM. This study assessed alterations in intracellular cytokine expression patterns in different T-lymphocyte subsets after ozone therapy in refractory IGM. Peripheral blood T lymphocyte subsets (CD8(+), CD4(+), CD4(+)CD25(+) CD127(-)) were analyzed via flow-cytometry for intracellular cytokine expressions IFN-gamma, TNF-alpha, IL-10, and TGF-beta before and after completion of 4-month systemic ozone therapy. Ozone therapy significantly increased the CD4(+)IFN-gamma(+) (p = 0.032), CD4(+)TNF-alpha(+) (p = 0.028), and the CD8(+) TNF-alpha(+) (p =0.012) T cells. In contrast, significant decreases in CD4(+) IL-10(+) (p = 0.047) and CD8(+)IL-10(+) T cells (p = 0.022) and CD4(+)CD25(+) CD127(-//low) Treg cells secreting TGF-beta (p = 0.005) were found after ozone therapy. When patients were analyzed according to the response to ozone therapy, patients with a complete remission were more likely to have increased CD3(-)CD16(+)CD56(+) natural killer cells (p = 0.0027) and decreased CD19(+)B lymphocytes (p = 0.046) following ozone therapy. Our results suggest that ozone therapy stimulated a T-helper-1 response associated with IFN-gamma production and downregulation of TGF-beta expression in CD4(+)CD25(+)CD127(-) Treg cells. These alterations in the immune system following ozone therapy can improve wound healing and restore immune dysfunction in patients with refractory IGM.
Keywords: Idiopathic Granulomatous Mastitis; IFN??; IL?10; Ozone Therapy; TGF??; TNF??